Strategy for Developing Cultural Literacy Based on Local Wisdom in Optimizing Students' Poetry Writing Skills - Ilfiani, Fitri; Syarifuddin, Syarifuddin; Ramadhan, Syahru (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research is motivated by the low poetry writing skills of elementary school students, especially in relating local cultural elements in literary works. In the midst of the challenges of globalization that are increasingly eroding regional cultural values, learning based on local wisdom is an important approach to instill cultural values while improving student literacy. This study aims to describe the strategy for developing cultural literacy based on local wisdom implemented at SDN 14 Sadia Bima City and assess its effectiveness in optimizing students' poetry writing skills. This type of research is descriptive qualitative research. The data sources come from classroom teachers, students, and documentation of literacy activities. Data collection techniques are carried out through observation, interviews, and documentation. Meanwhile, the data analysis technique uses the Miles and Huberman interactive model, namely data reduction, data presentation and conclusion drawn. The results of the study show that the strategies implemented by the school include the use of Bima folklore as teaching materials, poetry writing activities based on local culture, writing workshops with local artists, poetry exhibitions in Harvest Works activities, and collaborative community-based learning. These strategies have been proven to improve the quality of students' poetry in terms of structure, imagination, diction and connection with local cultural values This approach also increases students' motivation, confidence and love for their local culture. This shows that cultural literacy strategies based on local wisdom are feasible to be applied as a model of learning poetry in elementary schools.